Optimizing bladder cancer locoregional failure risk stratification after radical cystectomy using SWOG 8710. Issue 8 (3rd January 2014) - Christodouleas, John P.; Baumann, Brian C.; He, Jiwei; Hwang, Wei‐Ting; Tucker, Kai N.; Bekelman, Justin E.; Tangen, Catherine M.; Lerner, Seth P.; Guzzo, Thomas J.; Malkowicz, S. Bruce
<x xml:space="preserve">Abstract</x> BACKGROUND Clinical trials of radiation after radical cystectomy (RC) and chemotherapy for bladder cancer are in development, but inclusion and stratification factors have not been clearly established. In this study, the authors evaluated and refined a published risk stratification for locoregional failure (LF) by applying it to a multicenter patient cohort. METHODS The original stratification, which was developed using a single‐institution series, produced 3 subgroups with significantly different LF risk based on pathologic tumor (pT) classification and the number of lymph nodes identified. This model was then applied to patients in Southwest Oncology Group (SWOG) 8710, a randomized trial of RC with or without chemotherapy. LF was defined as any pelvic failure before or within 3 months of distant failure. RESULTS Patients in the development cohort and the SWOG cohort had significantly different baseline characteristics. The original risk model was not fully validated in the SWOG cohort, because lymph node yield was not as strongly associated with LF as in the development cohort. Regression analysis indicated that margin status could improve the model. A revised stratification using pT classification, margin status, and the number of lymph nodes identified produced 3 subgroups with significantly different LF risk in both cohorts: low risk (≤pT2), intermediate risk (≥pT3 with negative margins AND ≥10 lymph nodes identified), and high risk (≥pT3 with positive margins OR <10 lymph nodes identified) with 5‐year LF rates of 8%, 20%, and 41%, respectively, in the SWOG cohort and 8%, 19%, and 41%, respectively, in the development cohort. CONCLUSIONS A model incorporating pT classification, margin status, and the number of lymph nodes identified stratified LF risk in 2 different RC populations and may inform the design of future trials. Cancer 2014;120:1272–1280. © 2014 American Cancer Society.